PENGARUH STRATEGI KOMUNIKASI CORPORATE SOCIAL RESPONSIBILITY BUS TINGKAT MAYAPADA TERHADAP CORPORATE IMAGE PT. BANK MAYAPADA INTERNASIONAL TBK. (Universitas Negeri Surabaya, 2023)
Corporate image is an important thing for companies that always needs to be built and staked in society. One of important thingsin the effort to build a corporate image is the publication of company activities, eppecially CSR activities. CSR activities areimportant because in this case the company can be drecly involved with the community. The purpose of this paper is to identify theinfluence of CSR communication strategy on corporate image. The subject of this writing is the people of the city of Surabaya. Theare two variables in this writing, namely variable X (CSR communication strategy) and variable Y (corporate image). This writhinguses a quantitative approach. The technique used is the instrument test and classic assumption test (normality and hypothesis test).The result of this study show that H0 is rejected and H1 is accepted because of the T test (count t value > t table ; 30.847 > 1.980).So it can be concluded that there is an significant influence between CSR communication strategies on corporate image.